IMPLEMENTASI PROGRAM PENGEMBANGAN LISTRIK PEDESAAN OLEH DINAS PERTAMBANGAN DAN ENERGI KABUPATEN ROKAN HULU - Julianti, Lilis; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study was initiated by the low ratio Electrification Development Programmee electric rural areas in Rokan Hulu, it is characterized by many of the villages that have not getting electricity. In addition there is an imbalance between the proposal to electricity the countryside with the parties in the field. The purpose of this research is to figure out how the New Development Program electric rural areas by the Department of Mining and Energy of the Rokan Hulu, and to determine what the factors that affect the New Development Program electric rural areas by the Department of Mining and Energy of the Rokan Hulu.The research was carried out in the Department of Mining and Energy of the Rokan Hulu. The theory used in New Policy of Van Metter and Van Horn. As Van Metter and Van Horn said that there are six things to note that the implementation of the program can run well and achieve satisfactory results, size and purpose of Policy, Resource, Characteristics of Implementer Agent, Interorganisation Communication and activity of implementer, the Economic Environment, Social and Political Parties. The method used is descriptive approach a qualitative, and the techniques used in the collection of data is interviews, observations and documentation.This research result indicates that the New Development Program electric rural areas by the Department of Mining and Energy of the Rokan Hulu hasn't been going up, it can be seen from The purpose of a program that has not show fully because there are many rural communities that have not been getting the electricity, and is now the program has just reached Â± 60 %. The Program electric rural areas is still hampered by two factors : the limited budget the government and the lack of innovation in harnessing the potential of energy. If a limited budget then it would be hard for implementor to achieve the objectives of the program and innovation in the implementation of the program is still lacking then the success of the program to be getting longer.Keywords : Implementation, Programme, Electric rural areas.